140 Baseline variation in commonly used inflammatory neuropathy clinical outcome measures. Issue 6 (27th May 2022) - Keh, Ryan; Lilleker, James; Lavin, Tim; Gosal, David; Compton, Laura; Kapoor, Mahima; Carr, Aisling; Lunn, Michael
Abstract : Background: Reliable outcome measures are vital for guiding immunoglobulin therapy in inflammatory neuropathy. Disease-specific outcome measures exist with statistically sound minimal clinically important difference (MCID) to detect change (I-RODS:+/-4; grip strength:+/-8kPa). Scores generally remain stable in well-treated disease but variation occurs. Aims: To appreciate random variability of serially assessed grip strength, RODS and MRC-SS in clinically stable CIDP/MMN patients and explore early identification of non-random trends. Methods: We performed a longitudinal study of serial outcome measures from Manchester neurosciences immunoglobulin database (June 2009 - September 2012). We used first score on maintenance dosing as baseline, and increase in dose (g/kg/month) as indicative of meaningful clinical deterioration. We cal- culated mean/SD actual and percentage change(Δ) for grip(kPa), I-RODS(logit scale) and MRC-SS(/70) over periods of clinical stability. Results: 54/152 patients had sufficient stability: 39CIDP (9F), 15MMN (2F). Median age:66 years(mean:64.8, range:28–89). ΔRODS: 313 timepoints over 0.4–83.9months (median:27.4). Median change:0(0%), mean:- 0.08(0.17%), SD:4.3(8.9%). Δgrip: 569 timepoints over 0.9–98.1months (median:29.7). Δright grip median:- 1kPa(-0.11%), mean:-0.87(-0.96%), SD:5.34(5.9%). Δleft median:0kPa(0%), mean:-0.82(-0.91%), SD:5.70(6.3%). ΔMRC-SS: 75 timepoints over 1.9–52.7 months (median:10.7). Median change:0(0%), mean:0.59(0.83%), SD:4.73(6.8%). Analysis on trend identification and randomness is underway. Conclusion: Appreciation of magnitude of normal variation is clinically important. Early identification of trends will influence dosing decisions. ryan: keh@srft.nhs.uk|ABN Bursary 95